Analyzing Grammatical Error in Students' Recount Text Writing in Junior High School - Manik, Ni Putu Ines Marylena Candra; Arie Suwastini, Ni Komang (Humanis; Vol 24 No 3 (2020), 2020)
Having good grammar is one of important components in the mastery of writing skills. However, grammatical errors still become an important problem in writing, especially for EFL students. Therefore, this study aimed to find out the major types of grammatical errors; and to know the major source of grammatical errors in students’ recount text writing. This study was designed as a descriptive qualitative study. Recount texts written by the eighth-grade students of SMP Pelangi Dharma Nusantara in academic year 2019/2020 were used as the research subjects of this study. The data were identified and analyzed using  theory of error proposed by Dulay et al. (1982 ) about surface strategy taxonomy and theory of source of grammatical error proposed by Brown (2007)) . The findings showed that the major type of grammatical errors was omission, with the total of 171 errors or 37. 33% of the total errors. Meanwhile, the major source of grammatical errors was intralingual transfer which the total result was 248 or 43.43% error. Thus, it can be concluded that the most frequent grammatical errors that happened among the subject was error of omission, while the most common source of errors was intralingual transfer.